Digital technologies to accelerate the impact of climate smart agriculture by next-generation farmers in Africa - Mollel, Margareth; Quiroz, Luis Felipe; Varley, Ciara; Firestine, Alex; McLoughlin, Mary-Ellen; Kafunah, Jefkine; Kharkar, Shrutik; O'Farrell, Jemima; Ndlovu, Noel; Johnston, Angharad; McKeown, Peter C.; Brychkova, Galina; et al. (Frontiers in Sustainable Food Systems, 2025)
The adoption of digital technologies for scaling Climate-Smart Agriculture (CSA) practices can enhance agricultural productivity, food security, and livelihood sustainability of smallholder farmer communities in Africa. While digital agronomy supports for smallholder farmers present significant opportunities for strengthening agricultural extension systems, there are also significant barriers faced by smallholders in accessing and using digital agronomy services. Despite the rapid growth in phone and internet access in Africa, many smallholder farming communities and households lack effective access to the phone and internet services necessary for effective digital agronomy delivery. The digital divide that constrains smallholder farmers acts as a brake on the ambitions and targets for CSA scaling and for agricultural sector development across Africa, including in the Comprehensive Africa Agriculture Development Programme (CAADP) held in Strategy and Action Plan, and the Kampala CAADP Declaration on Building Resilient and Sustainable Agrifood Systems in Africa. Currently, there are a broad range of digital technologies (e.g., radio, mobile phone apps, video, mobile phone apps, animations, and social media platforms) that can be harnessed for scaling CSA amongst smallholder farmers, with a rapidly growing number of digital agronomy developers and providers. However, the affordability of phone and internet services for poorer smallholders, in addition to lack of technology infrastructure and digital literacy skills, remains a barrier to “last mile” delivery of effective digital agronomy services. As digital access becomes more affordable and digital agronomy systems become more powerful, pervasive (e.g., via social media and peer-to-peer training approaches) and localized (e.g., using artificial intelligence and machine translation), there is significant potential for digital agronomy systems to augment and strengthen national agricultural extension systems supporting smallholder farmers. In particular, digital agronomy services can help accelerate scaling of Climate-Smart Agriculture (CSA) practices for the millions of smallholder farmers who are most vulnerable to the unfolding climate crisis affecting their farming systems and livelihoods.